HUBUNGAN ANTARA SIKLUS MENSTRUASI DENGAN KADAR HEMOGLOBIN PADA REMAJA PUTRI - Siti Patonah, Siti Patonah; Fidrotin Azizah, Fidrotin Azizah (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2019)
The menstrual cycle is the time from the first day of menstruation until the arrival of the next menstrual period. Menstrual cycle normally lasts for 21-35 days, 2-8 days is the time of menstrual bleeding that ranges 20-60 ml per day. Research shows women with normal menstrual cycle is only found in two thirds of adult women. Hemoglobin is the red pigmented protein found in red blood cells. Normally the young Hemoglobin 13 g / dl and in girls 12 g / dl. Where the amount of hemoglobin in the blood is less than normal level is called anemia. In Indonesia, the prevalence of anemia was 57.1% suffered by young women, 27.9% suffered by women of childbearing age (WUS) and 40.1% suffered by pregnant woman.This study is a retrospective observational correlation with the approach of the samples taken by 47 students of grade IX SMPN1 SKW using simple random sampling technique. The technique of collecting data using questionnaires and examination Sahli hemoglobin. Statistical tests using the Mann-Whitney test. Based on statistical analysis using the Mann-whitney the result showed p value of 0.05 and r 0.98. Thus it can be seen that there is a significant relationship between the menstrual cycle with Hemoglobin levels in adolescent girls in SMP 1 SKW.